Gender Research and Food Policy: NGO Perspective - Cohen, Marc (2015)
IFPRI Policy Seminar “Beijing +20 and Beyond: How Gender Research Is Changing the Landscape of Food Policy” October 14, 2015. Presentation by Marc Cohen, Oxfam America.